Labor Mobility : An Investment in Human Capital Approach - Kottis, Athena (Relations industrielles / Industrial Relations, 1971)
The paper presents an explanation of the economic factors behind the geographic, occupational and industrial mobility of labor by considering movement from one area, occupation, or industry to another as an investment in human capital, requiring the incurrence of a certain cost and making possible certain returns, which are subject to various degrees of risk and uncertainty. It shows that both the traditional neoclassical theory and the institutional models present an incomplete picture of the factors affecting the mobility of labor and concludes that the factors deemed relevant by both theories are equally important in explaining the mobility of labor.